2021
DOI: 10.15408/tazkiya.v9i1.19272
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perceived Burdensomeness, Thwarted Belongingness, dan Religiusitas Terhadap Ideasi Bunuh Diri pada Lansia

Abstract: Suicidal ideation in elderly is rarely a society’s concern even though elderly is the age group most vulnerable to suicide. This study was conducted to prove the effect of perceived burdensomeness, thwarted belongingness, religiosity, and demographic factors (gender and education level) on suicidal ideation in the elderly. The subjects of this study were 230 respondents aged 60 years and over who were obtained using accidental non-probability sampling techniques. The measuring instrument used were the adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This value means that the elderly at the nursing home of Jember has significant suicidal ideation. This research is supported by research (Harahap & Amalia, 2021), that the elderly experience suicidal ideation but are in the low category. The risk of suicide is low in the elderly at the nursing home of Jember because the elderly can still interpret their lives.…”
Section: Suicide Risk In Elderly At Nursing Home Of Jembersupporting
confidence: 56%
See 1 more Smart Citation

Overview of Suicide Risk in Elderly at Nursing Home of Jember

Prasasti Puspita Avcafebriliani,
Aini Susumaningrum,
Susanto
et al. 2023
nhsj
“…This value means that the elderly at the nursing home of Jember has significant suicidal ideation. This research is supported by research (Harahap & Amalia, 2021), that the elderly experience suicidal ideation but are in the low category. The risk of suicide is low in the elderly at the nursing home of Jember because the elderly can still interpret their lives.…”
Section: Suicide Risk In Elderly At Nursing Home Of Jembersupporting
confidence: 56%
“…The result also showed that most of the elderly were widowed/widowed (47.4%), with 50% of the elderly at high suicide risk and 50% at low suicide risk. Research by Harahap & Amalia (2021), shows that the elderly who live alone have higher suicidal ideation than those who live with their partner. Meiner (2015) also mentions the elderly at risk of suicide, namely the elderly with widow/widower status and the elderly who live alone.…”
Section: Marital Statusmentioning
confidence: 99%

Overview of Suicide Risk in Elderly at Nursing Home of Jember

Prasasti Puspita Avcafebriliani,
Aini Susumaningrum,
Susanto
et al. 2023
nhsj
“…The significant difference in depression levels between early and late elderly can be caused by several things, including psychological changes in the elderly such as loneliness, loss, and grieving which can increase the incidence of depression. Loneliness can make a person susceptible to illness, depression, suicide, and even death in the elderly (Harahap et al, 2021).…”
Section: Resultsmentioning
confidence: 99%